Supplementary motor area—primary motor cortex facilitation in younger but not older adults - Green, P.; Ridding, M.; Hill, Keith; Semmler, J.; Drummond, P.; Vallence, A. (Elsevier Inc., 2018)
© 2018 Elsevier Inc. Growing evidence implicates a decline in white matter integrity in the age-related decline in motor control. Functional neuroimaging studies show significant associations between functional connectivity in the cortical motor network, including the supplementary motor area (SMA), and motor performance. Dual-coil transcranial magnetic stimulation studies show facilitatory connections between SMA and the primary motor cortex (M1) in younger adults. Here, we investigated whether SMA-M1 facilitation is affected by age and whether the strength of SMA-M1 facilitation is associated with bilateral motor control. Dual-coil transcranial magnetic stimulation was used to measure SMA-M1 connectivity in younger (N = 20) and older adults (N = 18), and bilateral motor control was measured with the assembly subtest of the Purdue Pegboard and clinical measures of dynamic balance. SMA-M1 facilitation was seen in younger but not older adults, and a significant positive association was found between SMA-M1 facilitation and bimanual performance. These results show that SMA-M1 facilitation is reduced in older adults compared to younger adults and provide evidence of the functional importance of SMA-M1 facilitation.